Medium of Instruction and Achievement in Social Studies among the Students of Gogan Secondary School, Pokhara - Adhikari, Sandeep (Kalika Journal of Multidisciplinary Studies, 2023)
This conference paper explores factors involved in the achievement of social studies in the basic level students of Pokhara Municipality. The objectives of the paper are to analyze the different factors associated with students’ achievement in learning social studies and to look for associations of mother-tongue education with the students’ achievement. A quantitative and applied research methodology with both primary and secondary sources of information was used. The primary data is collected via an online survey using a structured questionnaire. The data has been collected using researcher-administered online counseling and the distribution of online forms. Similarly, secondary data has been collected from different sources. The survey used a population of 155 students from one of the schools in Pokhara, Shree Gogan Secondary School, conveniently selected. The paper provides a theoretical basis showing that language choices are important for raising interest in the subject matter in students, which further increases the chances of attaining better grades. The students’ achievement is influenced by several factors, including linguistic, educational, social, and economic expediencies. At the time of the survey, it was observed that the students wanted some changes in the uses of the medium of instruction as well as the method of teaching. The study revealed that most respondents do not find English as a medium of instruction comfortable for study. Most respondents prefer their mother tongue as a medium of instruction. The paper concludes that mother-tongue education should be implemented rather than using an imposed medium of instruction (MOI).